2020
DOI: 10.1002/slct.201904532
|View full text |Cite
|
Sign up to set email alerts
|

SnS2/Bi4Ti3O12 Heterostructure Material: A UV‐Visible Light Active Direct Z‐Scheme Photocatalyst for Aqueous Phase Degradation of Diazinon

Abstract: In this study, a series of Z-scheme SnS 2 /Bi 4 Ti 3 O 12 heterostructure photocatalyst materials were synthesized by a two-step process. Initially, Bi 4 Ti 3 O 12 (BT) nanopellets with planar dimension of 350-400 nm were prepared by a facile combustion synthesis route. The SnS 2 nanoparticles (10-20 nm) were subsequently decorated over BT surface using a hydrothermal method. The heterostrucure materials possess orthorhombic BT and hexagonal SnS 2 crystalline phases with high interfacial contact and strong int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This was attributed to the rapid generation of the ˙OH and O 2 ˙ − under light irradiation, involving a Type-I bridged coupled Z-scheme charge transfer mechanism. Das et al 118 reported a Z-scheme SnS 2 /Bi 4 Ti 3 O 12 heterojunction photocatalyst material that exhibited good photocatalytic degradation activity for diazinon (DZN) under UV-visible light. This was attributed to the orthorhombic Bi 4 Ti 3 O 12 and hexagonal SnS 2 crystalline phases inside the material with a high interfacial contact and a strong interaction at the microscopic level, which improved the photoresponse range and enhanced the carrier separation.…”
Section: Advances In Semiconductor Photocatalystsmentioning
confidence: 99%
“…This was attributed to the rapid generation of the ˙OH and O 2 ˙ − under light irradiation, involving a Type-I bridged coupled Z-scheme charge transfer mechanism. Das et al 118 reported a Z-scheme SnS 2 /Bi 4 Ti 3 O 12 heterojunction photocatalyst material that exhibited good photocatalytic degradation activity for diazinon (DZN) under UV-visible light. This was attributed to the orthorhombic Bi 4 Ti 3 O 12 and hexagonal SnS 2 crystalline phases inside the material with a high interfacial contact and a strong interaction at the microscopic level, which improved the photoresponse range and enhanced the carrier separation.…”
Section: Advances In Semiconductor Photocatalystsmentioning
confidence: 99%
“…The metal sulfides such as Cu 2 S, Bi 2 S 3 , CdS, SnS 2 , and MoS 2 etc. have recently been studied as emerging photocatalysts because of their small band gap and higher negative conduction band potential. Due to improved electrical conductivity and redox characteristics, ternary metal sulfides have recently captured more attention from researchers over the binary metal sulfides . By altering their composition and stoichiometry, the band structure of ternary sulfides can be controlled, resulting in a broad range of light sensitivity and programmable redox potential .…”
Section: Introductionmentioning
confidence: 99%
“…Effective separation of the photogenerated carriers is therefore achieved in the local unit cell. 8 On this basis, several BiTO-based powder systems have been successfully reported over the years, for multiple photocatalytic purposes, [9][10][11][12][13][14][15][16][17][18][19] and recently BiTO has been employed as a catalyst also in the CO 2 photo-reduction reaction, producing CO, [20][21][22][23][24] methanol (CH 3 OH), 21 and methane (CH 4 ). 24 In addition to these already promising photo-catalytic performances, the distortion of the TiO 6 octahedra in the pseudo-perovskite blocks is responsible for the BiTO well-Please do not adjust margins Please do not adjust margins known ferroelectric behavior, 25 which has been proven to represent a strong driving force for bulk charge separation.…”
Section: Introductionmentioning
confidence: 99%